Analisis Kepuasan Pasien Terkait Kinerja Personal Perawat Di Rumah Sakit A - Ardi Peterson Seran; Sri Sundari; Marisi Pakpahan (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
This study aims to analyze the competence and personal performance of nurses on patient satisfaction in the Bandung Adventist Hospital. One of the problems that is often encountered in the provision of services in hospitals is the decline in patient satisfaction with the health services they receive in the service unit, this is usually caused by good or bad quality of services provided by nurses to patients in hospitals which indirectly can interfere with the level of patient satisfaction with the service. The design of this research is quantitative research using a cross-sectional study approach. The sample in this study was 20 patients at Bandung Adventist Hospital. Competence and personal performance variables as independent variables, patient satisfaction as the dependent variable. The research instrument used a questionnaire using a 1-4 Likert scale. This research uses multiple linear regression analysis. The results show that work competency and personal performance of nurses simultaneously have a positive effect on patient satisfaction. Nurses' work competency influences patient satisfaction, and nurses' personal performance influences patient satisfaction. The implication of this research is that one of the factors that causes moderate patient satisfaction is the nurse's work competency such as attitude and knowledge.